Legal Drafting Training for Creating Students' Ability to Make Agreements - Attas, Nasrah Hasmiati; Nasir, Citra; Saputra, Tri Eka; Abbas; Ibbank (Cendekiawan Indonesia Timur, 2022)
Legal drafting is an essential element in legal practice. Legal drafting relates to legal drafting made by legal subjects, both individuals and legal entities (authorized institutions), namely in the form of MoUs, cooperation agreements, and agreements/contracts. A complete understanding of legal drafting is essential for practitioners in various fields and agencies. Legal practitioners must often prepare legal drafts for their interests, clients, or institutions. Likewise, government agencies, state institutions, institutions, bodies, and commissions other than state institutions are interested in preparing legal drafting. Preparing legal drafting must consider the theories, principles, and rules regulated by statutory regulations and universal legal norms, standards, and practices. In this way, the validity of the agreed legal drafting product and the legal interests of the parties who drafted the legal drafting can be legally protected. However, many still need to understand how to prepare legal drafting correctly and legally. This training aims to help and provide students with understanding regarding making agreements. The output of this activity is 1) increasing students' legal awareness; 2) students can agree.